Ebselen reduces autophagic activation and cell death in the ipsilateral thalamus following focal cerebral infarction. (23rd July 2015) - Li, Yiliang; Zhang, Jian; Chen, Li; Xing, Shihui; Li, Jingjing; Zhang, Yusheng; Li, Chuo; Pei, Zhong; Zeng, Jinsheng
Highlights: Autophagy is involved in secondary thalamic damage after middle cerebral artery occlusion. We examined whether oxidative stress is involved in the thalamic autophagy activation. Antioxidant ebselen reduced oxidative stress, autophagy activation and secondary damage in the thalamus. Oxidative stress is associated with thalamic autophagy activation. Abstract: Previous studies have demonstrated that both oxidative stress and autophagy play important roles in secondary neuronal degeneration in the ipsilateral thalamus after distal middle cerebral artery occlusion (MCAO). This study aimed to investigate whether oxidative stress is associated with autophagy activation within the ipsilateral thalamus after distal MCAO. Sixty stroke-prone renovascular hypertensive rats were subjected to distal MCAO or sham operation, and were killed at 14 days after MCAO. Mn-SOD, LC3-II, Beclin-1 and p62 expression were evaluated by immunostaining and immunoblotting. Secondary damage in the thalamus was assessed with Nissl staining and immunostaining. The association of oxidative stress with autophagy activation was investigated by the antioxidant, ebselen. We found that treatment with ebselen at 24 h after MCAO significantly reduced the expression of Mn-SOD in the ipsilateral thalamus at 14 days following focal cerebral infarction. In parallel, it prevented the elevation of LC3-II and Beclin-1, and the reduction of p62. Furthermore, ebselen attenuated the neuronal loss and gliosis in the ipsilateral thalamus. These results suggested that ebselen reduced oxidative stress, autophagy activation and secondary damage in the ipsilateral thalamus following MCAO. There are associations between oxidative stress, autophagy activation and secondary damage in the thalamus after MCAO.